Judo combat: time-motion analysis and physiology - Franchini, E.; Artioli, G. G.; Brito, C. J. (International Journal of Performance Analysis in Sport, 2013)
The understanding of time-motion and physiological responses to judo combat is important to training organization. This review was based on search results using the following terms: "judo and competition", "judo and physiology", "judo and randori", and "judo and time-motion analysis", "judo and combat", "judo and match" and "judo and biochemestry". The effort-pause ratio during judo combats is between 2:1 and 3:1, with 20s and 30s effort periods and 10s of pauses. Thus, judo combats rely on all three metabolisms, with the anaerobic alactic sytem being reponsible by the short duration powerful actions during technique applications, the anaerobic lactic system being responsible for the maintainance of high-intensity actions during longer periods (e.g., grip dispute), while the aerobic system is responsible for the recovery processes between high-intensity actions and matches. Training prescription must consider these demands and a muscle-specific action analysis may help to direct the proper approach to improve judo athletes' performance. In general, lower-body is involved in short-term high-intensity actions during technique executions, while upper-body muscle groups are involved in both strength-endurance and power actions. As many muscle groups perform different actions during the match, a high cardiovascular demand is also observed in judo.